Популяційна структура та ресурси черевоногого молюска Nacella concinna (Strebel, 1908) у прибережних водах Української антарктичної станції “Академік Вернадський”, архіпелаг Аргентинські острови, Західна Антарктика - Березкіна, Анна Євгенівна; Berezkina, A.Ye. (Харків: ХНУ імені В.Н. Каразіна, 2021)
Berezkina A.Ye. Population structure and resources of the gastropod mollusk Nacella concinna (Strebel, 1908) in the coastal waters of the Ukrainian Antarctic Station "Academik Vernadsky", Argentine Islands archipelago, West Antarctica. Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Biology, Speciality 091 – Biology (09 – Biology). – V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2021. The thesis is dedicated to new data on the population structure of the gastropod mollusk N. concinna for the entire island system of the Argentine Islands, West Antarctica. Patterns of limpet distribution in this water area taking into account the morphological and genetic population structure. The phylogeny of the genus Nacella and possible regions of origin and distribution are reconstructed. The role of mollusks in Antarctic ecosystems, data on resources and the possibility of its use as an environmental indicator are determined. Three morphotypes of N. concinna with different shell sculptures in the water area of the Ukrainian Antarctic Station "Academik Vernadsky" were identified. The first morphotype has a shell with a smooth glossy dark surface, the second - a classical form with clear radial ribs, the third – with concentric rings and a white top of the shell. It was found that morphotypes do not differ in morphometric parameters, do not have genetic differentiation, which indicates that the three morphotypes of N. concinna belong to the same species.
Population structure and resources of the gastropod mollusk Nacella concinna (Strebel, 1908) in the coastal waters of the Ukrainian Antarctic Station "Academik Vernadsky", Argentine Islands archipelago, West Antarctica
У дисертації розкрито нові дані щодо структури популяції черевоногого молюска N. concinna для цілої острівної системи Аргентинських островів, Західна Антарктика. Встановлено закономірності розповсюдження молюска в дослідженій акваторії з урахуванням морфологічної та генетичної структури популяції. Реконструйовано філогенію представників роду Nacella і можливі регіони походження і шляхи поширення. Визначено роль молюска в антарктичних екосистемах, дані про ресурси та можливість його використання як індикатора стану навколишнього середовища. Виявлено три морфотипи N. concinna з різною скульптурою раковини в акваторії Української антарктичної станції «Академік Вернадський»: перший морфотип – раковина з гладкою глянцевою темною поверхнею, другий – класична форма з чіткими радіальними ребрами, третій – з концентричними кільцями та білою вершиною раковини. Встановлено, що морфотипи не відрізняються за морфометричними показниками, не мають генетичної диференціації, що свідчить про приналежність трьох морфотипів N. concinna до одного виду.
Keywords: Nacella concinna; антарктичний лімпет; структура популяції молюска; філогенія; баркодинг; молекулярні годинники; молюск-асоційовані бактерії; біполярне розповсюдження; ензими бактерій; Західна Антарктика; Nacella concinna; Antarctic limpet; mollusk population structure; phylogeny; barcoding; molecular clock; mollusk-associated bacteria; bipolar distribution; bacterial enzymes; West Antarctica